2006
DOI: 10.1007/s10661-006-0988-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Atmospheric Aerosol (PM10) at a Semi-arid Urban Site: Influence of Terrestrial Sources

Abstract: Atmospheric aerosol (PM(10)) measurements were made at a regional representative semi-arid urban site, Tirupati, India over one-year period i.e. from October, 2001 to September, 2002. The samples were collected on polyflex filters, and analyzed for the major water-soluble ions - F, Cl, NO(3), SO(4), Na, NH(4), K, Ca and Mg, employing ion chromatograph. The average mass of PM(10) is found to be 32.75 mug/m(3) with a total water-soluble aerosol load (total anion + total cation) of 13.56 mug/m(3). Composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…The aerosol mass and BC seasonality observed at NCO-P is similar to the variations observed at other Indian sites, with lower values during the monsoon season, mostly due to wet scavenging, and larger ones in the winter and pre-monsoon periods (Chandra Mouli et al, 2006;Ganguly et al, 2006). In the Indogangetic plain, at Gadanki station (India, 375 m a.s.l., 13.5 • N, 79.2 • E), Krishnan and Kunhikrishnan (2004) observed that the atmospheric boundary layer height was maximum during the pre-monsoon period, and minimum during the winter months.…”
Section: Seasonal Variations Of Pms and Bcsupporting
confidence: 75%
See 1 more Smart Citation
“…The aerosol mass and BC seasonality observed at NCO-P is similar to the variations observed at other Indian sites, with lower values during the monsoon season, mostly due to wet scavenging, and larger ones in the winter and pre-monsoon periods (Chandra Mouli et al, 2006;Ganguly et al, 2006). In the Indogangetic plain, at Gadanki station (India, 375 m a.s.l., 13.5 • N, 79.2 • E), Krishnan and Kunhikrishnan (2004) observed that the atmospheric boundary layer height was maximum during the pre-monsoon period, and minimum during the winter months.…”
Section: Seasonal Variations Of Pms and Bcsupporting
confidence: 75%
“…As expected, the aerosol mass values observed at NCO-P were much lower (at least one order of magnitude) than the corresponding ones measured everywhere else in the Indian Subcontinent: the annual average mass of PM 10 was 33 µg m −3 (annual average, with similar seasonality as NCO-P) in Tirupati, South of India (Chandra Mouli et al, 2006), 74 µg m −3 in Agra (Khemani et al, 1982), 66 µg m −3 in Ahmedabad (Ganguly et al, 2006) both cities in the IndoGangetic Plain. This reflects the influence of the brown clouds, as well as the larger transcontinental pollution over South and East Asia .…”
Section: Comparison With Other Sitessupporting
confidence: 64%
“…The low frequent detection of Gram negative bacteriais attributed to their sensitivity to the air environment 41 , and the initial shock due to desiccation after aerosolization 42 .Firmicutes, Proteobacteria and Actinobacteria are common bacterial types in the urban environment, where Gammaproteobacteria and Betaproteobacteria have been regularly identified 1 . Mouli et al 43 found airborne Gram positive bacteria in the range of 60% -90% of the total bacterial population, in Tirupati, India; however Bacillus constituted 47.62% and Acinetobacteria 14.27% in the atmosphere of El Taief, Saudi Arabia 44 . Bacillus, Micrococcus and Staphylococci differed from place to place depending on the micro-environment 45 .…”
Section: Discussionmentioning
confidence: 99%
“…F -is often considered to be a constituent of emission from coal combustion. Brick kilns which are coal fed in nearby localities could be the likely source of F - (Mouli et al, 2006;Salve et al, 2007).…”
Section: Diurnal Variabilitymentioning
confidence: 99%
“…This indicates brick kilns and soil as the possible sources of these chemical species. F -may be attributed to coal fed brick kilns and Mg from soil (Mouli et al, 2006;Salve et al, 2007). Some NO 3 -and SO 4 2-could also have come as contributions from soil (Wang et al, 2003;Tare et al, 2006).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%